(untitled) (The Strategic Review for Southern Africa, 2020)
Zuma’s ascendancy to the South African Presidency coincided with the lingering global economic crisis of 2007-2009, which affected many of the Western economies. By this time, China experienced a rapid economic growth and became a potential partner for commodities exporting countries like South Africa. As such, it became a potential partner in the face of declining commodity demand from the West. Against this background, Zuma deepened South Africa’s ties with China to rescue the domestic economy. China has since received much attention in Zuma’s administration resulted in many scholars emanating from International Relations and other cognate academic disciplines and members of the media describing the move as a shift in South Africa’s foreign policy. This article employs Afrocentricity as an alternative theoretical framework to interrogate the question as to whether closer ties between the two countries marked a shift or Zuma prioritised China. Methodologically, this is a desktop article that relied on secondary data and employed an Afrocentric qualitative research methodology to establish whether the deepening relations led to a shift in South Africa’s foreign policy or China received priority in Zuma’s administration.